Pengembangan Platform Digital Melalui E-Katalog dalam Rangka Diseminasi Informasi pada PT. Uola Pandawa Sejahtera di Yogyakarta - Putri, Saffir; Azizah, Azizah; Hermawan, Iwan; W, Dika Vivi (Jurnal Kridatama Sains dan Teknologi, 2024)
Digital Transformation (DT) is not ust a technological opportunity but also an urgent necessity to meet the evolving expectations of society. Nowadays, businesses are required to adopt more efficient and effective methods in managing information and communicating with customers. Digital Marketing, as a crucial implementation of DT, enables companies to interact with customers through digital channels such as social media, email, and websites. In this context, PT Uola Pandawa Sejahtera, operating in the creative industry, faces challenges in disseminating product and service information. Using traditional costly and inflexible printed catalogs and lagging behind competitors who have embraced digital marketing, they decided to transition to the innovation of a web-based e-catalog. The aim of this research is to design an e-catalog platform for PT Uola Pandawa Sejahtera using the Waterfall method. The e-catalog replaces printed catalogs, allowing the company to update information in real-time, enhance customer interactions, and reduce operational costs. Test results show that the e-catalog provides easy access to information, boosts engagement, and reduces printing costs. Recommendations involve regular updates, SEO optimization, and admin training. This research significantly contributes to PT Uola Pandawa Sejahtera, enabling them to remain relevant in the digital age, provide superior customer service, and cut printing expenses.